Canine pheochromocytoma: a case report - Caballero Salcedo, Miguel; Duarte Rodríguez, Luz (Spei Domus, 2011)
This paper reports a case of pheochromocytoma in a 20-year old mongrel breed dog female submitted to a consultation at the Small Animal Vet Hospital “Dr. Santiago Reyes Amaya” in Bucaramanga. Patient had clinical neurological symptoms (seizure episodes and ataxia), among other symptoms. Clinical examination found a patient with severe symptoms of pain, tachypnea, tachycardia, tetraparesis, nystagmus, anterior-and-posterior limb proprioception loss, impaired mental status, hyper-reflexia, and abdominal pain. The neurological examination of cranial nerves I-III-V-VII-XI resulted in abnormality, cephalic and cervical inclination towards left side. A hematological examination was performed, including complete blood count and blood biochemistry (liver and renal profile), and also skull radiographies, but everything was normal. After reporting neurological status with a medical report of poor prognosis, and taking into account the patient’s general condition and age, owner decided to perform euthanasia. So patient was available to the clinic with the owner permission to perform autopsy for academic purposes. The goal of this paper is review general aspects of canine pheochromocytoma, reporting a case.